PHYLOGENETIC ANALYSIS OF 16S rRNA GENE FRAGMENT OF ANTIBIOTIC-PRODUCING PLS 76 ISOLATE - Mulia Aria Suzanni; Amelya Yolanda; Nurdin Saidi; Febriani Febriani; Teuku Mohamad Iqbalsyah (Universitas Syiah Kuala, 2018)
Exploitation of extremophiles as novel bioactive compounds sources has been increasing. The aim of this study was to evaluate the activity and the class of antibiotic produced by a thermo-halophilic isolate PLS 76, as well as to identify the genotype of the isolate. The activity was determined by a disc diffusion method, while the antibiotic class was determined qualitatively by chemical reactions using ninhydrin, iodine vapour and potassium iodine. The genotype was determined by sequencing the 16S rRNA gene fragment and the phylogenetic tree from the sequence data. The results showed that PLS 76 was a Gram-negative bacterium and able to produce polypeptide antibiotic, which showed a slight activity on E. coli and S. aureus. Sequence alignment of the 16S rRNA gene fragment showed that PLS 76 was most related to Geobacillus kaustophilus. These results may be used to utilise the isolated for further antibiotic study.